2016
DOI: 10.21475/ajcs.2016.10.09.p7892
|View full text |Cite
|
Sign up to set email alerts
|

Growth, yield and fruit quality of ‘Maçã’ banana under different rates of phosphorus fertilization

Abstract: The aim of this study was to evaluate the agronomic performance and fruit quality of 'Maçã' banana cultivar. A field experiment was conducted to study the effect of phosphorus (P) on the cultivar. The study area presents a subtropical climate, where the mean temperature is 22°C; and the mean rainfall is 1377 mm. The experiment was conducted from November 2012 to May 2014. The experiment design was totally randomized, consisting of six treatments (0, 40, 60, 80,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(16 reference statements)
2
3
0
2
Order By: Relevance
“…The adjusted linear regressions between the midrib of the 3 rd leaf of the banana tree in function of the application of P doses in the soil were significant at 10; 5 and 5% probability in the first, second and third cycle, respectively (Figure 1).The adjusted regressions between the petiole of the 3 rd leaf and the P doses applied to the soil were significant at 5% probability only in the second and third cycle ( Figure 2) and the adjusted linear regressions between the midrib of the 7 th leaf in function of P doses application in the soil were significant at 5% probability only in the third cycle ( Figure 3). There were no significant regression adjustments between the limb of the 3 rd leaf in function of the P doses applied to the soil in the three production cycles, confirming the results obtained by Silva & Rodrigues (2013) and Bolfarini et al (2016). The average P contents found in the blade of the 3 rd leaf were 1.9; 1.8 and 1.7 g kg -1 in the first, second and third cycles, respectively, presenting within the range of sufficiency (1.5 -1.9 g kg -1 ) established by Silva et al (2002).…”
Section: Crop Productionsupporting
confidence: 84%
See 1 more Smart Citation
“…The adjusted linear regressions between the midrib of the 3 rd leaf of the banana tree in function of the application of P doses in the soil were significant at 10; 5 and 5% probability in the first, second and third cycle, respectively (Figure 1).The adjusted regressions between the petiole of the 3 rd leaf and the P doses applied to the soil were significant at 5% probability only in the second and third cycle ( Figure 2) and the adjusted linear regressions between the midrib of the 7 th leaf in function of P doses application in the soil were significant at 5% probability only in the third cycle ( Figure 3). There were no significant regression adjustments between the limb of the 3 rd leaf in function of the P doses applied to the soil in the three production cycles, confirming the results obtained by Silva & Rodrigues (2013) and Bolfarini et al (2016). The average P contents found in the blade of the 3 rd leaf were 1.9; 1.8 and 1.7 g kg -1 in the first, second and third cycles, respectively, presenting within the range of sufficiency (1.5 -1.9 g kg -1 ) established by Silva et al (2002).…”
Section: Crop Productionsupporting
confidence: 84%
“…According to these authors, this part of the leaf may not be suitable for use in the diagnosis of P content in the banana tree. Bolfarini et al (2016) found Similar results. For Lahav and Turner (1983), the analysis of the petiole or the midrib may be better than that of the limbs to diagnose the P content in the banana tree.…”
Section: Crop Productionsupporting
confidence: 69%
“…Consequently, it could impair plant development. Phosphates tend to reduce zinc solubility, zinc phosphate formation in soil, and induce iron and manganese deficiency by reducing their mobility in plant tissues (Bolfarini et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is present in more than 130 countries, reaching more than 116 million tons produced worldwide (Amah et al, 2019;FAOSTAT, 2021). Its success and high consumer demand are due both to the versatility, in terms of modality of use (processed, fried, boiled, in natura), and to the attributes related to flavor, smell, nutritional value, price, hygiene and ease of consumption (Bolfarini et al, 2016). Additionally, it can be produced throughout the year, what makes it a more attractive species for producers.…”
Section: Introductionmentioning
confidence: 99%